Effect of phosphate amendments on improving the fertilizer efficiency and reducing the mobility of heavy metals during sewage sludge composting. (1st April 2019) - Wang, Xiankai; Zheng, Guodi; Chen, Tongbin; Shi, Xiaoxiao; Wang, Yuewei; Nie, Erqi; Liu, Junwan
Abstract: Composting has been globally applied as an effective and cost-efficient process to manage and reuse sewage sludge. In the present study, four different phosphates as well as a mixture of ferrous sulfate and monopotassium phosphate were used in sewage sludge composting. The results showed that these phosphate amendments promoted an increase in temperature and the degradation of organic matter as well as reduction on nitrogen loss during 18 days of composting. In addition, ferrous sulfate and phosphate had a synergistic effect on reducing nitrogen loss. The contents of total phosphorus and available phosphorus in the compost with addition of 1% phosphate were 40.9% and 66.1% higher than the compost with control treatment. Using the BCR (Community Bureau of Reference) sequential extraction procedure, the addition of calcium magnesium phosphate significantly reduced the mobility factor of Cd, Zn and Cu by 24.2%, 1.7% and 18.8%, respectively. The mobility factors of Pb were increased in all samples, but the monopotassium phosphate treated sample exhibited the greatest Pb passivation ability with the lowest mobility factor increase (1.8%) among all treatments. The X-ray diffraction patterns of compost samples indicated that the passivation mechanism of Cu and Zn may be the forming CuFeS2 and ZnCu(P2 O7 ) crystals during sewage sludge composting. The germination index showed that the compost of all treatments was safe for agricultural application; the germination index of the calcium magnesium phosphate treatment was 99.9 ± 11.8%, which was the highest among all treatments. Graphical abstract: Image 1 Highlights: Phosphate promoted temperature rise and organic matter degradation during composting. Ferrous sulfate and phosphate had synergistic effect on reducing nitrogen loss. Total P and available P content increased 40.9% and 66.1% by adding 1% phosphate. Heavy metals were passivated with the addition of phosphate amendments. All compost products in this study were safe for land application.